Comparative Study on Fetomaternal Outcome after Lower Uterine Segment Caesarean Section and Vaginal Delivery in Eclamptic Patient (Faridpur Medical College Journal, 2020)
Eclampsia has a high prevalence in our country with a high mortality rate. Eclampsia is uniquely a disease of pregnancy and regardless of gestational age. It is recognized that termination of pregnancy is the only definitive care of pathophysiological event in eclampsia. This study was done to observe fetomaternal outcome in Lower Uterine Segment Caesarean Section (LUCS) and vaginal delivery in eclamptic patient. This cross sectional analytical study was carried out in eclampsia department of Obst and Gyane in Dhaka Medical College Hospital from July 2016 to June 2018. A uniform protocol was followed in all cases to have appropriate history, physical findings and laboratory investigations. In this study 98.0% patients were conscious on admission in group I and 96.0% in group II. This study showed significant difference in recurrence of convulsion after delivery between two groups. Recurrence of convulsion was 30% in vaginal delivery group and 6% in the cesarean section group. Total complications were found in 46.0% and 16.0% patients in group I and group II respectively in this study. The difference was statistically significant (p